Respuesta :

Answer:

The answer to your question is: the first option

Step-by-step explanation:

          Equation                     3abc + b = 5                 solve for c

                                              3abc = 5 - b                  pass b subtracting

                                              3ac = (5 - b)/b              pass b dividing

                                              3c  = (5 - b) / ab            pass a dividing

                                              c = (5 - b) / 3ab            pass 3 dividing

Answer:

the first one is correct

Step-by-step explanation:

i took the test and it was correct

ACCESS MORE